Etika Digital dalam Perspektif Pendidikan Agama Islam - Ikhsan Setiawan; Fadloli; Abdul Chalim; Astrifidha Rahma Amalia (STID Raudlatul Iman Sumenep, 2025)
The digital era has brought significant changes in various aspects of life, including easier access to information and communication. However, negative impacts such as digital addiction, the spread of misinformation, hate speech, and online bullying have also increased. In this context, digital ethics has become an important aspect that users of technology must understand and apply. Islamic Religious Education (PAI) plays a strategic role in raising awareness and providing guidance on digital ethics based on Islamic values, such as trust, responsibility, and etiquette in communication. This research aims to formulate the concept of digital ethics from an Islamic perspective and analyze the contribution of PAI in educating students about digital ethics. The method used is qualitative research with a literature study approach, focusing on the analysis of literature from books, academic journals, and relevant previous research. The results indicate that digital ethics in Islam emphasizes values of honesty, politeness, and responsibility in media use. Additionally, PAI plays a crucial role in shaping students' critical attitudes toward digital content and guiding them in using technology ethically. This research is expected to serve as a reference for developing a more adaptive PAI curriculum that meets the challenges of the digital era. Era digital membawa perubahan signifikan dalam berbagai aspek kehidupan, termasuk kemudahan akses informasi dan komunikasi. Namun, dampak negatif seperti kecanduan digital, penyebaran informasi palsu, ujaran kebencian, dan perundungan online juga semakin meningkat. Dalam konteks ini, etika digital menjadi aspek penting yang harus dipahami dan diterapkan oleh pengguna teknologi. Pendidikan Agama Islam (PAI) memiliki peran strategis dalam membentuk kesadaran dan memberikan panduan etika digital yang berlandaskan nilai-nilai Islam, seperti amanah, tanggung jawab, serta adab dalam berkomunikasi.Penelitian ini bertujuan untuk merumuskan konsep etika digital dalam perspektif Islam serta menganalisis kontribusi PAI dalam mengedukasi mahasiswa tentang etika digital. Metode yang digunakan adalah penelitian kualitatif dengan pendekatan studi pustaka, yang berfokus pada analisis literatur dari buku, jurnal ilmiah, serta penelitian terdahulu yang relevan.Hasil penelitian menunjukkan bahwa etika digital dalam Islam menekankan nilai-nilai kejujuran, kesopanan, dan tanggung jawab dalam bermedia. Selain itu, PAI memiliki peran penting dalam membentuk sikap kritis mahasiswa terhadap konten digital serta membimbing mereka dalam menggunakan teknologi secara etis. Penelitian ini diharapkan dapat menjadi referensi bagi pengembangan kurikulum PAI yang lebih adaptif terhadap tantangan era digital.